An mRNA assay system demonstrates proteasomal-specific degradation contributes to cardiomyopathic phospholamban null mutation - Eduarde Rohner; Nevin Witman; Jesper Sohlmer; Erwin De Genst; William E. Louch; Makoto Sahara; Kenneth R. Chien (BMC, 2021)
Abstract Background The human L39X phospholamban (PLN) cardiomyopathic mutant has previously been reported as a null mutation but the detailed molecular pathways that lead to the complete lack of detectable protein remain to be clarified. Previous studies have shown the implication between an impaired cellular degradation homeostasis and cardiomyopathy development. Therefore, uncovering the underlying mechanism responsible for the lack of PLN protein has important implications in understanding the patient pathology, chronic human calcium dysregulation and aid the development of potential therapeutics. Methods A panel of mutant and wild-type reporter tagged PLN modified mRNA (modRNA) constructs were transfected in human embryonic stem cell-derived cardiomyocytes. Lysosomal and proteasomal chemical inhibitors were used together with cell imaging and protein analysis tools in order to dissect degradation pathways associated with expressed PLN constructs. Transcriptional profiling of the cardiomyocytes transfected by wild-type or L39X mutant PLN modRNA was analysed with bulk RNA sequencing. Results Our modRNA assay system revealed that transfected L39X mRNA was stable and actively translated in vitro but with only trace amount of protein detectable. Proteasomal inhibition of cardiomyocytes transfected with L39X mutant PLN modRNA showed a fourfold increase in protein expression levels. Additionally, RNA sequencing analysis of protein degradational pathways showed a significant distinct transcriptomic signature between wild-type and L39X mutant PLN modRNA transfected cardiomyocytes. Conclusion Our results demonstrate that the cardiomyopathic PLN null mutant L39X is rapidly, actively and specifically degraded by proteasomal pathways. Herein, and to the best of our knowledge, we report for the first time the usage of modified mRNAs to screen for and illuminate alternative molecular pathways found in genes associated with inherited cardiomyopathies.